Democratic Procedures in the CCP's Cadre Selection Process: Implementation and Consequences*. (24th November 2015) - Zeng, Qingjie
Abstract: Since the early 1990s, the Chinese Communist Party (CCP) has put in place a series of measures to allow more Party members to participate in the cadre selection process. "Intra-party democracy" was promoted as a remedy to solve the corruption and social tension that resulted from overly concentrated personnel power. How effective are these formal procedures in constraining the appointment power of core Party leaders and institutionalizing the influence of a larger group of cadres? Drawing on archival research, interviews and quantitative data, this paper examines two components of intra-party democratic reform: "democratic recommendation, " which serves as a gateway to cadre promotion, and the semi-competitive elections at Party congresses. This in-depth study finds that the efforts to expand bottom-up participation are hindered by loopholes in formal regulations, informal practices and the frequent rotation of Party officials. Meanwhile, the reform measures have brought changes to the personnel system by complicating the Party secretaries' exercise of appointment power and altering the incentives of ambitious cadres. The implementation of intra-party democracy could improve the vitality of one-party rule, and its ebbs and flows imply a divide within China's top leadership over the direction of political change. 摘要: 自二十世纪九十年代初以来, 中国共产党引入了一系列措施, 让更多的党员参与到干部选拔工作中来。中共希望以 "党内民主" 的措施来纠正因人事权过分集中而导致的用人腐败和官民关系紧张。这些党内民主的程序能否有效限制党委主要领导的用人权, 并将广大党员干部的参与制度化? 基于文档研究、访谈和量化数据, 本文考察了党内民主改革的两个组成部分: 作为干部提拔必经程序的民主推荐以及党代会期间的半竞争性选举。研究发现, 由于正式制度本身的缺陷、制度以外的非正规操作以及官员的频繁异地调动, 自下而上的党员参与受到了阻碍。同时, 这些改革措施也改变了党委书记行使任命权和党员干部追求晋升的方式。党内民主的贯彻执行可能让一党执政更加稳固, 而党内民主的兴衰起伏也反映了中共高层内部对于政治改革方向的分歧。